Virtual reality vs. imagery: comparing approaches in guided meditation - Jo, Minkyung; Kim, Eunha; Lee, Jaeyeon (Frontiers in Psychology, 2024)
Introduction This study compared the influence of virtual reality (VR)-based and traditional (e.g., imagery-based) guided meditation on stress and concentration levels among South Korean adults. In addition, we examined whether concentration levels differed between individuals who are new to meditation and those who are experienced. Methods Seventy participants were randomly assigned to either the VR or imagery condition, where they engaged in breathing and waterfall concentration meditation. Pretest and posttest measures of heart rate (HR), galvanic skin response (GSR), negative affect, and concentration during meditation were recorded. Results Both VR- and imagery-based guided meditation significantly reduced HR, GSR, and negative affect. However, no significant differences in outcomes were observed between the two groups. Still, participants in the VR condition reported higher concentration levels during meditation, particularly novice meditators. In addition, qualitative feedback indicated that VR-based meditation was more effective in inducing positive emotions, such as calmness and enjoyment. Discussions While both VR- and imagery-based guided meditation effectively reduce stress and negative affect, VR-guided meditation shows promise for enhancing concentration, particularly for novice meditators.